High-Flow Nasal Cannula Versus Pressure Support Ventilation for Spontaneous Breathing Trials in High-Risk Patients Before Extubation: A Clinical Study - Hina, Nida Haider, Afia Arshed Dodhy, Afshan Nisar, Muhammad Athif Akram, Muhammad Aleem Haider (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The spontaneous breathing trial technique may influence extubation outcomes in high-risk mechanically ventilated patients. Pressure support ventilation is commonly used, but it may overestimate post-extubation respiratory capacity. High-flow nasal cannula may provide better comfort and oxygenation while allowing a more physiological assessment before extubation. Objective: To evaluate high-flow nasal cannula vs pressure support ventilation as options for spontaneous breathing trials in high-risk patients before scheduled extubation. Methods: This prospective randomized comparative clinical trial was conducted in the Intensive Care Unit, Lahore General Hospital / Ameer-ud-Din Medical College, Lahore, from June 2021 to June 2022. A total of 150 mechanically ventilated high-risk patients were randomized into two equal groups. Group A underwent a 30-minute spontaneous breathing trial using high-flow nasal cannula, while Group B received pressure support ventilation. The primary outcome was successful extubation within 72 hours. Results: The rate of successful extubation within 72 hours was greater in the high-flow nasal cannula group than in the pressure support breathing group (85.3% vs. 70.7%; RR: 1.21; 95% CI: 1.02–1.44; p = 0.048). The high-flow nasal cannula was correlated with a reduced respiratory rate, decreased dyspnoea score, elevated comfort score, increased ventilator-free days, and a shorter duration of ICU stay. Reintubation and death rates were decreased in numerical terms; however, not statistically significant. Conclusion: High-flow nasal cannula was associated with improved extubation success and better physiological tolerance compared with pressure support ventilation in high-risk mechanically ventilated patients. Keywords: High-flow nasal cannula; pressure support ventilation; spontaneous breathing trial; extubation; mechanical ventilation; intensive care unit.